Gender Diversity: Green Banking and Financial Performance - Yuniarti, Rina; Riswandi, Pedi; Junaidi, Ahmad (UNKLAB Business School, 2025)
Unbalanced industrialization has damaged the environment and resulted in natural and industrial disasters. Environmentally conscious banking has become a target for investors, leading to increased financial performance. The aim of this research is to examine the effect of green banking on financial performance, moderated by gender diversity. This study employs a quantitative approach. The population consists of 12 sharia banks in Indonesia from 2017 to 2023. The research sample includes 72 companies, using a saturated sampling technique. The data is secondary, sourced from the annual reports of sharia banks. Data analysis was conducted using SEM-PLS, processed with WarpPLS 7.0. The results indicate that green banking has a significant positive effect on financial performance. Additionally, gender diversity moderates the effect of green banking on financial performance. These findings emphasize the importance of integrating green banking practices and gender diversity to improve the financial performance of sharia banking. This research contributes to the development of sustainable banking strategies and highlights the relevance of gender diversity in creating added value for Sharia financial institutions.